(untitled) (Journal of NELTA, 2018)
In this an era of technology, new technologies particularly computer, multimedia, mobile phone and the internet offer possibilities for overcoming geographical and cost barriers in teaching and learning. This study attempts to trace the use of technology in teaching English at the S.S.C. (Secondary School Certificate) level in Bangladesh. It also focuses on the impact of using technology in teaching and learning English. Eight teachers and 60 students from four private schools in Dhaka city were selected to survey the use of technology in teaching the English Language. The researchers employed the mixed methods research to carry out the study where two sets of questionnaires for the teachers and the students and a semi-structured interview only for the teachers were used to collect data. The findings showed that using technology in teaching has both the positive and the negative impacts. Teachers like to use technology in their classroom but limited time and lack of training and technical support from the authority hamper the mode of teaching. The students also feel comfortable in technology affiliated classroom, but sometimes they fail to catch the concept clearly as they become inattentive due to the lack of proper engagement of the teachers in the classroom.